Exploring the efficacy of mindmend: an innovative mental health support app for autistic adolescents and their caregivers - Zannat, Nahreen; Mahmud, Murni (MyHCI-UX, 2023)
The adolescents with mild ASD and their caregivers often have unique needs which are usually ignored in conventional mental health therapy interventions. ‘MindMend’: An innovative smart phone application which brings together mental health care and teenagers with mild autism spectrum disorder and their carers. This app consists of social skills training modules, an emotion regulation app, a CBT app, a goal-setting module, and is completed with the progress tracking functionality. There is also an opportunity to meet with others in social media setting. Early trials suggest that it can help reduce stress for care-givers as well as symptoms of autism. “MindMend” aspires to be an eclectic intervention that promotes healthy mentality by acknowledging the cultural and religious variations. It underscores the significance of comprehensive care for adolescent autistics and their custodians.